Ternate sebagai ruang perjumpaan antarbudaya: Studi komunikasi antara orang Ternate dan Bugis - Rakhmat, Rakhmat; Kaddas, Badruddin; Burhan, Burhan (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study aims to examine the dynamics of intercultural communication between the people of Ternate and the Bugis community, who have long resided in the region. As a port city with a rich history as a center of trade and royal power, Ternate serves as a social space that facilitates encounters, interactions, and negotiations between cultures. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that communication between Ternate and Bugis people takes place within a historical framework shaped by Islamic values, economic ties, and social solidarity. Cultural adaptation patterns are evident. Despite differences in cultural identity, both communities foster harmony through inclusive communicative practices and mutual respect for local values. This study affirms that Ternate is not merely a geographic location but a cultural arena that enriches the collective identity of its people.